Factors Affecting Photodynamic Therapy and Anti-Tumor Immune Response - Hamblin, Michael R.; Abrahamse, Heidi (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Photodynamic Therapy (PDT) is a cancer therapy involving the systemic injection of a Photosensitizer (PS) that localizes to some extent in a tumor. After an appropriate time (ranging from minutes to days), the tumor is irradiated with red or near-infrared light either as a surface spot or by interstitial optical fibers. The PS is excited by the light to form a long-lived triplet state that can react with ambient oxygen to produce Reactive Oxygen Species (ROS) such as singlet oxygen and/or hydroxyl radicals, that kill tumor cells, destroy tumor blood vessels, and lead to tumor regression and necrosis. It has long been realized that in some cases, PDT can also stimulate the host immune system, leading to a systemic anti-tumor immune response that can also destroy distant metastases and guard against tumor recurrence. The present paper aims to cover some of the factors that can affect the likelihood and efficiency of this immune response. The structure of the PS, drug-light interval, rate of light delivery, mode of cancer cell death, expression of tumor-associated antigens, and combinations of PDT with various adjuvants all can play a role in stimulating the host immune system. Considering the recent revolution in tumor immunotherapy triggered by the success of checkpoint inhibitors, it appears that the time is ripe for PDT to be investigated in combination with other approaches in clinical scenarios.
Keywords: photosensitizer